Evaluation of Marginal and Internal Fit in CAD/CAM-Fabricated Indirect Restorations - Helmy, Ayman Helmy; Salama, Mohamed Samy; Botros, Sara Adel; Ahmed, Hend Sayed (Journal of Neonatal Surgery, 2025)
Objectives: This study investigated the effect of marginal adaptation and internal fit of premolar teeth restored with indirect overlays, fabricated from different CAD/CAM materials (lithium-disilicate and composite blocks). Materials and Methods: Twenty-two intact premolars with standardized concave chamfer overlay preparation were divided into two groups (n= 18) Group (A): lithium disilicate blocks and Group (B): composite blocks. All groups cemented with dual cured resin cement. After 24h of storage at 37°C followed by thermocycling. Marginal gap evaluation evaluated using a stereomicroscope at x50 magnification at 4 points at each surface. Specimens were then sectioned mesiodistally to assess internal fit. Statistical analysis was performed using student t-test at p<0.05. Results: Composite blocks showed higher but statistically similar marginal and internal gap mean values. Conclusions: Using composite blocks in fabrication of overlay restorations provided comparable marginal and internal gap results to lithium disilicate blocks.